Selenium seed priming enhanced the growth of salt-stressed Brassica rapa L. through improving plant nutrition and the antioxidant system - Hussain, Saber; Ahmed, Shakil; Akram, Waheed; Li, Guihua; Yasin, Nasim Ahmad (Frontiers in Plant Science, 2023)
Various abiotic stresses may affect the germination, growth, and yield of direct-seeded vegetable crops. Seed priming with some effective antioxidative mediators may alleviate such environmental stresses by maintaining uniformity in seed germination and improving the subsequent health of developing seedlings. Salt-induced stress has become a limiting factor for the successful cultivation of Brassica rapa L., especially in South East Asian countries. The present study was performed to elucidate the efficacy of selenium (Se) seed priming in mitigating salt-induced oxidative stress in turnip crops by reducing Na+ uptake. In this study, we used three different levels of Se (Se-1, 75 μmolL-1; Se-2, 100 μmolL-1; and Se-3, 125 μmolL-1) alone or in combination with salt (200 mM). Conspicuously, salinity and Se-2 modulated the expression levels of antioxidant genes, including catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), and ascorbate peroxidase (APX). The upregulated expression of stress-responsive genes alleviated salt stress by scavenging the higher reactive oxygen species (ROS) level. The stress ameliorative potential of Se (Se-2=100 μmolL-1) enhanced final seed germination percentage, photosynthetic content, and seedling biomass production up to 48%, 56% and 51%, respectively under stress. The advantageous effects of Se were accredited to the alleviation of salinity stress through reducing the MDA, proline and H2O2 level. Generally, Se-2=100 μmolL-1 treatment was more effective in enhancing the growth attributes of B. rapa as compared to Se-1= 75 μmolL-1 and Se-3=125 μmolL-1 concentrations under salt-stressed and non-stressed conditions. Findings of the current study advocate the application of Se seed priming technique as an economical and eco-friendly approach for salt stress mitigation in crops grown under saline conditions.